Global Hunger Index: The challenge of hunger: Facts, determinants, and trends - Wiesmann, Doris; Weingärtner, Lioba; Schöninger, Iris (Welthungerhilfe, 2006)
It’s a bitter reality that in a world that is growing closer all the time, hunger, undernutrition, and abject poverty are still rife. The poorest of the poor lack a sufficiently influential voice to make their fundamental concerns be heard. It’s therefore essential that knowledge, political will, and action be brought together in the fight against hunger. The collaboration between Deutsche Welthungerhilfe and the International Food Policy Research Institute (IFPRI) contributes to this endeavour. While there has been progress in the fight against hunger in a number of regions in the world, pledges made to eradicate hunger are being repeatedly broken. The target of halving the proportion of hungry people in the world as agreed by 189 heads of state in the 2000 Millennium Goals will not be met: it’s estimated that if trends continue at the current pace, there will still be around 610 million people suffering from hunger by the year 2015 – that is, 32 million more than set as a target by the heads of state. The considerably more ambitious goal set at the 1996 World Food Summit in Rome – to reduce the number of hungry to 412 million people – can be seen as more desirable but the world is not on track to achieve it.